Pengaruh Variasi Nilai Konstruksi Terhadap Pengendalian Proyek - Jumali, Muhamad Abdul; Maubila, Alorinda Zantia; Pradipta, Arjuna Raffi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes the influence of constructin value variation on project control effectiveness in Indonesia using a quantity explanatory research design. The data were obtained from the statistics Indonesia (BPS) 2023 report, specifically the dataset on constructin categories. Descriptive analysis reveals highly extreme value variations with several large-scale outliers. Pearson correlation analysis indicates very strong relationship (≥ 0,97) among value categories, suggesting simulatneous escalatin in multi component projects. The findings imply that higher construction values requier more complex control mechanism, including Earned Value Management (EVM), structured risk mitigation, and strist change-order management. This study recommends adopting value-based project control classifications to enhance the effectiveness of cost anda schedule oversight and to support optimal construction project performance.